2010
DOI: 10.1080/09540101003758954
|View full text |Cite
|
Sign up to set email alerts
|

Stability and immunoreactivity of glycinin and β-conglycinin to hydrolysis in vitro

Abstract: The present study was to compare the stability and immunoreactivity of glycinin and b-conglycinin to hydrolysis with pepsin, trypsin or cooperation of the two enzymes for different time intervals (0.5, 1, 15, 30, 60 and 120 min) at different ratios of enzyme/substrate (1:100, 1:10, 1:1 and 10:1) in vitro. The results showed that the immunoreactivity was positively related with stability of glycinin (r 00.776, PB0.05) and b-conglycinin (r 00.851, PB0.05). B polypeptide chain of glycinin was resistant to hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
4
18
1
Order By: Relevance
“…The enzymatic hydrolysis of glycinin and β-conglycinin with tryptic and peptic enzymes showed that, at a low pH, glycinin was denatured and more susceptible to hydrolysis, while β-conglycinin was denatured at higher temperature and became more hydrolyzed in contrast to glycinin, which was not affected. However, the IgG-binding capacity was never completely removed [40,41]. In our research, the immunoreactive proteins were not recognized in only one hydrolysate (SHB HVP), while, in the other two, they were found.…”
Section: Discussioncontrasting
confidence: 56%
“…The enzymatic hydrolysis of glycinin and β-conglycinin with tryptic and peptic enzymes showed that, at a low pH, glycinin was denatured and more susceptible to hydrolysis, while β-conglycinin was denatured at higher temperature and became more hydrolyzed in contrast to glycinin, which was not affected. However, the IgG-binding capacity was never completely removed [40,41]. In our research, the immunoreactive proteins were not recognized in only one hydrolysate (SHB HVP), while, in the other two, they were found.…”
Section: Discussioncontrasting
confidence: 56%
“…Several researchers have investigated the structure and functional properties changes of SPI, glycinin (11S), and β-conglycinin (7S) during heat treatment [9][10][11][12][13]. Hu et al [14] found that the structure of glycinin was maintained when heated at the temperature range of 20-60 • C. However, heating above 80 • C significantly decreased the content of β-sheets and increased the content of random coils [15,16]. Natarajan et al [17] revealed that the first denaturation temperature of β-soy conglycinin was 65 • C. When the temperature of the protein rose to 75 • C, the content of β-sheet structure no longer increased.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of flavourzyme and pancreatin hydrolysis was the most effective on β ‐hexosaminidase inhibition followed by alcalase and pancreatin, respectively (Figure ). MBPHFP 270 , MBPHA 90 and MBPHP 90 significantly (Zhao et al, ) reduced allergic activity when compared to other groups. The effects of MBPHFP, MBPHA and MBPHP on cell viability were determined using the MTT assay (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, some legume allergens exhibit very high stability to peptic digestion. For example, soybean β ‐conglycinin was not destroyed after 60 min of pepsin hydrolysis (Astwood et al, ; Zhao et al, ). Ara h 1 is a major allergen found in peanut; in vitro gastric digestion led to rapid breakdown into smaller fragments, but still retained its allergenicity to induce histamine release in basophils (Eiwegger et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation